Effects of Single-Nucleotide Polymorphisms in Cytokine, Toll-Like Receptor, and Progesterone Receptor Genes on Risk of Miscarriage - Anastasiia Razdaibiedina; Mykhaylo Khobzey; Victoria Tkachenko; Iryna Vorobiova (Obstetrics and Gynecology International)
Spontaneous abortion is a complex, multifactorial pathology, where various genetic, neural, endocrine, and immunological factors are involved. Cytokines, Toll-like receptors, and progesterone receptors play critical roles in embryonic implantation and development. A delicate, stage-specific equilibrium of these proteins is required for successful pregnancy outcome. However, genetic variation from one individual to another results in variation in levels of Th1/Th2 cytokines, strength of identification of infectious agents by Toll-like receptors, and quality of progesterone recognition. Thus, a complex study encompassing effects of major SNPs of cytokine, TLR, and PGR genes on the risk of miscarriage is needed. In this study, we investigated SNPs of 9 genes (TLR2 G753A, TLR4 C399T, TLR9 G2848A, TGF-β1 C509T, PGR PROGINS, IL-6 G174C, IL-8 C781T, IL-10 C592A, and TNFα G308A) in 106 women, whose pregnancy ended in miscarriage, and 74 women, who delivered in term without any pregnancy complication. All participants are from Ukrainian population. As a result, TLR9 and IL-10 SNPs have been found to play critical roles in the development of spontaneous abortion. TLR2, TLR4, IL-6, IL-8, and PGR SNPs were identified as secondary factors that can also affect the risk of miscarriage. There was no association found between TGF-β1 and TNFα polymorphisms and miscarriage.